An Analysis of Strategic Planning’s Impact on the Performance of a Selected Nigerian Manufacturing Firm. - Abalaka, J.N; Ajiteru,S.A.R; Sulaiman T.H (Harmony Management: International Journal of Management Science and Business, 2025)
Over the past 20 years, as globalization has fully embraced industry, the study that evaluates the impact of strategic planning on manufacturing companies' performance has garnered a lot of interest from academic researchers and business practitioners. the spotlight. However, there aren't many empirical research looking into the connection between corporate performance and strategic management in Nigeria. Therefore, this study's primary goal was to present more proof of how strategic management (SM) affects Nigeria's manufacturing sectors' performance. Five sizable listed manufacturing companies in the city of Lagos were chosen. 50 respondents from the chosen firms were purposefully chosen to complete a structured questionnaire, which provided the study with primary data. In order to achieve the stated particular objectives of the study, the obtained data were analyzed using descriptive analysis, correlation analysis, and Analysis of Variance (ANOVA). The outcome demonstrated that strategic management significantly impacted the operational performance and profitability of the certain manufacturing companies. Additionally, there was a strong correlation between the firms' level of rivalry and strategic management. According to the study's findings, strategic management is essential for improving business performance in Nigeria's manufacturing sectors.